Development and testing of precast concrete beam-to-column connections with high-strength hooked bars under cyclic loading. Issue 14 (October 2019) - Yang, Hui; Guo, Zhengxing; Yin, Hang; Guan, Dongzhi; Yang, Sen
A traditional reinforcing detail—hooked bars anchored in the joint core—for the bottom bars in precast beams was improved by using small-diameter high-strength bars to reduce the steel congestion in the cast-in-place connection zone. Five full-scale beam-to-column connections, including a monolithic specimen, were tested under reversed cyclic loading. The primary test variables were the type of beam longitudinal bars, manner of roughening the inner surface of the precast U-shell, presence or absence of the small-diameter stirrups inside the U-shell, and height of the precast columns. An analysis of the strength, ductility, stiffness, and energy dissipation showed that the proposed connection exhibited a comparable, although slightly inferior, seismic performance relative to the monolithic connection. Among the precast specimens, the existence of additional stirrups slightly improved the total performance. The use of high-strength steel bars as beam top longitudinal bars further decreased the loading capacity and energy dissipation. The air bubble film technique used to roughen the interfaces ensured the structural integrity.